Kesesuaian Minat Karir dengan Keputusan Memilih Jurusan di Perguruan Tinggi - Abdiyatul Hasanah (Journal of Classroom Action Research, 2023)
Students compete to enroll in tertiary institutions with the majors they are interested in. Making a lot of students wrong in is a very important thing. Irene Guntur: "So that there is no more movement, don't let it be when you are in college. Student career planning is defined as "the process by which they take the form of direction. Expanding the horizons of knowledge acquired through scientific disciplines requires the development and maturity of interests and careers. This study uses a descriptive quantitative method because in this thesis there is data that is processed and the results are described. Selection of decisions based on a compiled personality inventory. the decision to choose a major regarding learning activities in lectures. In this study, there is a concordance between career interests and the decision to choose a major in tertiary institutions with data on the BK major of 27% of 105 students, the engineering department of 11% of 70 students and the arts major of 10% of 40 students. The decision to choose this major is based on Holland's theory. In this study, it can be concluded that there is a suitability of career interests with the decision to choose a major in college